Routine follow-up transjugular liver biopsy in Fontan patients: technical considerations and safety of an initial case series and literature review - Guido Mandilaras; Zora Meyer; Richard Mühlberg; Annabell Braun; Nikolaus A. Haas; Andre Jakob; Robert Dalla Pozza; Moritz Wildgruber; Marcus Fischer (Frontiers Media S.A., 2023)
IntroductionPatients with Fontan palliation are susceptible to congestive hepatopathy and Fontan-associated liver disease (FALD) because of hemodynamic changes. The staging of liver fibrosis involves various methods, including invasive biopsy. Transjugular liver biopsy (TJLB) offers a less invasive alternative, enhancing liver disease surveillance in routine cardiac catheterization. We detail the technical aspects, share initial outcomes, and discuss existing literature.Methods/resultsDuring routine follow-up cardiac catheterization indicated by hemodynamic or clinical alterations, four patients aged between 16 and 26 years with univentricular Fontan circulation and three patients with biventricular circulation underwent TJLB during routine surveillance catheterization. The examinations were performed under conscious sedation and local anesthesia without general anesthesia. Jugular access was obtained at the site of liver localization, and a 5 F multipurpose catheter was inserted into the liver veins. After hand angiography to delineate the local hepatic venous anatomy, an exchange wire was used to place the bioptome, and three consecutive biopsies were performed. There were no complications, especially perforation or bleeding. The technical success rate was 100%, with all obtained samples appropriate for histopathological diagnostics. The total additional procedure time was less than 20 min.ConclusionTJLB is an attractive alternative method for obtaining liver specimens in the scope of FALD care. We believe that it should be performed during routine hemodynamic evaluations in Fontan patients and can be performed safely with very low additional time expenditure. As the biopsy site is intravascular, the risk of external bleeding or hematoma is significantly reduced despite the high intrahepatic pressures and the usually impaired coagulation profile in these patients. Based on our initial experience and the lower complication rates compared with other techniques, TJLB should be considered a standard approach in these patients and used more often during the long-term follow-up of Fontan patients. It can be performed in the same setting whenever a hemodynamic assessment of patients with congenital heart defects is required.